The Transformation Of Learning During Covid-19 Pandemic Towards The New Normal Era - Ahmad Hatip (Universitas Muhammadiyah Surabaya, 2020)
Abstract. The purpose of this literature review is to describe the transformation in learning that occurred during the Covid-19 pandemic. The planned learning transformation process includes the transformation of the use of learning technology and learning media in distance learning, transformation of learning designs, transformation of learning models and transformation of learning assessments so that learning remains effective and efficient. In the transformation process, there are several learning problems, including: teacher and student competencies to use technology are still weak and learning facilities and the internet are not evenly distributed. The good impact of the Covid-19 pandemic is the ability of educators and students to grow well. Educators and students are